2016
DOI: 10.1002/lary.26097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of idiopathic subglottic stenosis for Mycobacterium species

Abstract: Rationale Idiopathic subglottic stenosis (iSGS) is an unexplained obstruction involving the lower laryngeal and upper tracheal airway. Persistent mucosal inflammation is a hallmark of the disease. Epithelial microbiota dysbiosis is found in other chronic inflammatory mucosal diseases; however, the relationship between tracheal microbiota composition and iSGS is unknown. Objectives Given the critical role for host defense at mucosal barriers, we analyzed tissue specimens from iSGS patients for the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 51 publications
2
72
1
1
Order By: Relevance
“…Given our single institution cohort, risk factors for recurrence remain elusive. Further work with the NoAAC may prove fruitful in elucidating risk factors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given our single institution cohort, risk factors for recurrence remain elusive. Further work with the NoAAC may prove fruitful in elucidating risk factors …”
Section: Discussionmentioning
confidence: 99%
“…The disorder primarily affects otherwise healthy females aged 30 to 50 years. Recent data suggests that both activation of inflammatory pathways and possible pathogenic bacteria may be contributing to the disease process . It is also theorized that hormones may play a role in disease; however, there is no clear link aside from a predilection toward females .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Another potential explanation for the increase in INF-Υ expression in iSGS is the propensity for bacterial colonization by mycobacterium species in iSGS. 8 Previous studies have demonstrated that Mycobacteriums antigenicity invokes a robust release of INF-Υ from T-cells, natural killer cells, and macrophages. 18,19 Like IL-4, the role of this increased INF-Υ expression in iSGS is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The most predominant etiology of LTS is iatrogenic (iLTS), in which intubation injury to the epithelium promotes prolonged subepithelial inflammation and subsequently fibroblast proliferation and collagen deposition . This dysregulated wound‐healing response is driven by complex signaling between epithelial cells, immune mediators, and fibroblasts, which stimulates deposition of excessive collagen, leading to airway narrowing . Mild airway restriction secondary to this narrowing impacts quality of life, and in severe cases requires surgical intervention to relieve the resultant dyspnea.…”
Section: Introductionmentioning
confidence: 99%